Pengaruh Berbagai Bentuk Intervensi Apoteker terhadap Kepatuhan Pengobatan dan Kualitas Hidup Pasien Rawat Jalan Skizofrenia : Narrative Review - Sambada, Annisa; Putri, Mukarromah Dita; Mulyati, Noviani Ayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Schizophrenia is a global issue with a significant increase in recurrence, affecting approximately 23 million people or 1 in every 345 individuals worldwide, with recurrence rates increasing from 28% in 2019 to 54% in 2021[2]. This narrative review examined the literature from 2015–2024 from PubMed and Google Scholar with inclusion criteria of pharmacist interventions in outpatient schizophrenia patients, the use of assessment instruments such as MARS, PANSS, and WHOQOL-BREF, and the reporting of quantitative outcomes related to adherence and quality of life. Seven studies that met the criteria showed that pharmacist counseling can significantly improve medication adherence. In the Si-Care model, adherence rates increased from 77.38% to 97.57% (an increase of 20.19%; p = 0.000). Higher effectiveness was seen in longer-duration interventions, interactive methods such as home visits, and implementation involving collaboration with psychiatrists, which also supported improvements in quality of life. However, variations in study design resulted in diverse findings, and single-session interventions tended to be less optimal than ongoing support. Without counseling, adherence rates remained low, at around 65%. Overall, the available evidence confirms the benefits of pharmacist counseling, but further research is needed to standardize intervention models and evaluate the long-term impact on outpatients with schizophrenia.